Urate-Lowering Therapy May Prevent the Development of Coronary Artery Disease in Patients With Gout - Yen, Fu-Shun; Hsu, Chih-Cheng; Li, Hsin-Lun; Wei, James Cheng-Chung; Hwu, Chii-Min (Frontiers in Medicine, 2020)
Substantial evidence has demonstrated a close relationship between hyperuricemia and cardiovascular (CV) diseases, but few studies have explored the possibility of using urate-lowering therapy (ULT) to attenuate the development of CV diseases. To compare the risks of incident coronary artery disease (CAD), stroke, and heart failure (HF) between ULT users and nonusers in patients with gout, we conducted a retrospective cohort study from the population-based National Health Insurance Research Database in Taiwan. In total, 4072 patients with gout were included between 2000 and 2012. The overall incident rates of CAD, stroke, and HF were compared between 2036 ULT users and 2036 matched non-users. The incident rates of incident CAD were 1.3 and 1.7 per 100 person-years for ULT users and nonusers. ULT users had a lower adjusted hazard ratio (aHR) for CAD (aHR: 0.7, 95% confidence interval [CI]: 0.55–0.89) compared with nonusers. ULT users also had a lower aHR for incident stroke (aHR: 0.68, 95% CI: 0.5–0.92) compared with nonusers. ULT had a neutral effect on the risk of incident HF (aHR: 0.92, 95% CI: 0.58–1.45). Uricosuric agents had a significant effect on the prevention of CAD and stroke development. The protection against the development of CAD by uricosuric agents appeared to have a dose-response trend. Our study demonstrated that ULT could significantly lower the risks of incident CAD and stroke. We recommend that patients with gout receive ULT to lower the burden of CV diseases.